IMPLEMENTASI KURIKULUM TINGKAT SATUAN PENDIDIKAN BIDANG STUDI IPS PADA MADRASAH TSANAWIYAH SWASTA AL-FURQAN BAMBI KABUPATEN PIDIE - Hasballah .; Jamaluddin Idris; Nasir Usman (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2012)
Abstract: Unit Level Education Curriculum (KTSP) curriculum constitutes one of constituent in teaching and learning process. This research intent to inspect, observe and describe the implementation Unit Level Education Curriculum in particular area Social study at MTs Swasta Al Furqan Bambi Pidie Regency, as follows: (1) Program developmental activities syllabi, RPP and SKL; (2) Material preparations for teaching; (3) Learning performings; and (4) Estimation perfor-ming/evaluations. This research utilizes qualitative descriptive method. Data collecting tech that is utilized is observation, interview and documents study. Subjects in this observational were principal, vice principal, and social study teachers. Result observational to point out that KTSP's implementation on that social study can be seen of: (1) Syllabus makings performing and RPP which made by Social study teacher done by personaland groups in MGMP, but they experience interference in determine indicator in point; (2) Material preparations teach that did by Social study teacher as LKS and module, really help student in completes each competences; (3) Learning performing that did by teacher utilizing close to get center on child (child centered) through active learning, creative, effective, and rejoicing by use of infrastucture media and medium whatever available; (4) Evaluate learningthat did by Social study teacher in forms process estimation as dry run of daily, common dry run or final examination, and task estimation as application of task that performed by individual or group.Key word: Social Study and KTSP